The Impact of Oral Glutamine Supplementation on Prevention of Nosocomial Infections in Preterm Infants - Gholamali Maamouri; Fatemeh Zegheibizadeh; Fatemeh Khatam; Hasan Boskabadi (Mashhad University of Medical Sciences, 2016)
Background: In the recent decades, the prevalence of nosocomial infections in neonates has grown and almost 21% of preterm neonates experience these kinds of infections. Some factors were proposed to have a protective effect against neonatal infections through promoting the development of the immune system of the newborn. This study aimed to evaluate the efficacy of oral glutamine supplementation in management of neonatal sepsis. Methods: Neonates were randomly allocated to case and control groups. The infants in the case group received 0.3 g/kg/day glutamine, every eight hours from three days of age to 28 days. Hospital stay duration and occurrence of necrotizing enterocolitis (NEC) as well as sepsis were recorded for each patient. Data were analyzed using SPSS version 16. Results: In general, 105 neonates were enrolled in the study, 52 of who were allocated to the glutamine group and 53 neonates assigned to the control group. The results showed that 52 (49.5%) cases were male and 53 (50.6%) were female with mean gestational age of 30±2 weeks. Life threatening infections occurred more commonly in the control group (P=0.036). Six neonates (11.5 %) in the glutamine group and eight (15.1 %) in the control group developed clinical sepsis (P=0.592). NEC occurred only in the control group (P=0.118). Mean durations of hospital stay in the glutamine and placebo groups were 20±12 days and 26±18 days (P=0.065), respectively. Mean durations of oxygen therapy were 6±5 days and 16±11 days for the glutamine and control groups, respectively (P=0.039). Conclusion: Oral glutamine administration reduced life threatening infections and duration of receiving supplemental oxygen.